Bifactor Invariance Analysis of Student Conceptions of Assessment Inventory - Matos,Daniel Abud Seabra (2019)
Abstract Student conceptions of the purposes of assessment are an important aspect of self-regulated learning. This study advances our understanding of the Student Conceptions of Assessment Inventory (SCoA) by examining the generalizability of the factorial structure of the SCoA using bifactor analysis and conducting cross-cultural invariance testing between Brazil and New Zealand. Eight different models were specified and evaluated, with the best model being adopted for invariance testing. This research adds to our understanding of the cross-cultural properties of the SCoA because the introduction of the bifactor model resulted in metric equivalence between countries, which had previously had only partial metric equivalence. Future studies should attempt to create more items around several SCoA constructs.